Interpretation of Student Data in Web-Based 21st Century Learning in Junior High School - Rahayu Kurniawati, Nenden Sri; Herdiana, Dodi (Journal of Education, 2025)
Education is an important component in sustaining a nation or state. Preparing superior human resources is one of the country's ideals, including Indonesia, especially with the development of the current era of the Industrial Revolution 4.0 in the 21st century. Education, especially learning, is a fundamental thing that must be strengthened to achieve the desired goals. This study aims to see the extent of student data interpretation related to Web-Based online learning (web-learning). The prepared data includes students in State Junior High Schools in Garut from grade 7 to grade 9. The sample in this data is as many as 500 students from various junior high school classes. The results collected by the researcher are data obtained from several questionnaire questions related to online learning (web learning). The findings from the data taken show that approximately of students agree or even strongly agree with online learning. Students understand how important Information and Communication Technology is to support fulfilment in learning to improve student competence in the 21st century. The response of students to learning using web-learning was very positive, with around 52.80% stating that they strongly agreed and agreed. Web learning can increase students towards improving their learning. This can be shown by the results of their survey, which is 55.4% of students who answered yes and strongly agree. And The response of students to teachers who use web learning is very good, which can be seen from the results of survey number 15 around 61.4%.